The proposal of the new absolute: Iberico and the philosophical essay within the Peruvian avant-garde (1916-1932) - Reyes Álvarez, Carlos (2025)
The article explores the philosophical proposal of Mariano Iberico’s new absolute, within the Peruvian avant-garde movement. Iberian, he belonged to an intermediate generation: between that of the Nine Hundred and the Centennial, at the beginning of the 20th century. He also participated in the emergence and dynamics of the avant-garde movement in the country, through a set of ideas and proposals, from philosophy. We will take care of this. First we will address some general concepts about European avant-garde, since it was there where it emerged, as a response to the crisis of the prevailing order, supported by philosophical positivism. Later, we will deal with the Peruvian avant-garde movement, which is known more for its literary expression, however, here we question this and consider that it was a broader and more diverse movement. And finally, the last chapter, we dedicate to analyzing the philosophical proposal of Mariano Iberico’s new absolute.